Teacher Overinvolvement and Student Depression among Junior High School Students in Taiwan - Fen Fen Huang; Cou Chen Wu; Chang Ya Hu; Sun Shen Yang (The Scientific World Journal)
This study examines depression in students at public high schools in Taiwan. The purpose of this study is to examine which student-level and teacher-level variables affect student depression due to teacher emotional overinvolvement and other factors. A survey instrument adapted and translated from existing surveys was distributed to 1,479 Taiwanese adolescents aged 13—15 years and 172 teachers from 10 public junior high schools in the city of Taipei. The hierarchical linear model (HLM) was used for a cross-level analysis of the data. The HLM shows that student-level measures account for most of the variance. Teacher emotional overinvolvement and core self-evaluations are the preponderant influences on student ratings. In terms of teacher-level variables, the effects of teacher involvement, teacher depression, and teacher educational background on student-level variables are strong and significant. The findings of this study recommend the development of a comprehensive counseling system for teachers and students.